A Fault-Resilient Implementation of Three Level Npc Igct-Based Converters - Rocha, Anderson Vagner; França, Gleisson J.; Santos, Manoel E. dos; Paula, Hélder de; Filho, Braz J. Cardoso (Eletrônica de Potência, 2011)
This paper presents a strategy for protecting high power IGCT-based converters which are currently used in a wide range of drive applications. The protection of such converters against internal faults has been addressed in the technical literature, but the main focus has been on the solutions to disconnect the converter from the mains. In this paper, the short circuit current paths through the power devices are identified and studied from the perspective of keeping the overall repair cost after a fault to a minimum. It is shown that a preferred short-circuit current path that limits the thermal energy in all IGCTs to safe levels exists. Furthermore, it is demonstrated that it is possible to guarantee, through proper busbar geometry and/or device selection, that the short-circuit current stress can always be moved to the power diodes. Simulation results are presented to support all the discussions and conclusions, avoiding the costs and risks of tests on a medium voltage prototype.